The Particularities of Employees’ Green Ethical Behavior in the Oil and Gas Sector - Adriana Burlea-Schiopoiu; Camelia Olivia Timpa (Behavioral Sciences)
The article aims to evaluate the particularities of the green, ethical behavior of employees from the oil and gas sector in light of climate change and sustainable development. We employed a quantitative research approach and partial least squares structural equation modeling (PLS-SEM) using SmartPLS4 software (version 4.1.0.9) to test our conceptual model. The results demonstrate that employees’ green, ethical behavior influences how the rules of conduct contribute to an organization’s sustainable development, and employees’ green, ethical behavior is influenced by the ethical values assumed by an organization through its code of ethics and integrity. Moreover, employees’ green, ethical behavior and ethical values mediate the relationships between other factors, such as, for example, employees’ knowledge of the particularities of a company’s ethical values, their degree of compliance with the rules of conduct within the organization, and how their compliance with the rules of conduct is reflected in the organization’s sustainable development. The reflection of ethical issues in an organization’s sustainable development depends on a systemic approach to the formal and informal behavior of managers and employees. The theoretical implications of our research represent a starting point for extending our knowledge of employees’ green ethical behavior in terms of their acceptance and application of rules and ethical principles in close connection with the sustainable development of an organization. This study’s practical implications consist of awareness of the role that managers play in developing certain internal instruments (i.e., codes of ethics and integrity) to be understood and accepted by employees, with power of their personal example in motivating employees to improve their green ethical behavior. In conclusion, the manifestation of green, ethical behavior in employees does not automatically lead to sustainable development if it is not based on a set of ethical values and rules of conduct clearly understood and accepted by these employees.